1952
DOI: 10.1017/s0025315400003714
|View full text |Cite
|
Sign up to set email alerts
|

On the use of antibiotics for isolating bacteria-free cultures of marine phytoplankton organisms

Abstract: In the course of some studies on the kinetics of growth and the biochemical activities of a marine diatom it became desirable to obtain bacteria-free cultures. The classical method of obtaining such pure algal cultures involves either repeatedly washing single cells in sterile medium or obtaining discrete bacteria-free algal colonies by growth on a solid medium. Both these methods have been widely applied to fresh-water species by Pringsheim (1946) and others, whilst Chu (1946) has used both methods with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
5

Year Published

1954
1954
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 5 publications
0
32
0
5
Order By: Relevance
“…The concentration of penicillin G was selected by reference to the work of Cviic (1953) who showed that which would control many species of marine bacteria. Spencer (1952) had already shown that it was relatively harmless to Isochrysis at this concentration.…”
Section: Resultsmentioning
confidence: 88%
“…The concentration of penicillin G was selected by reference to the work of Cviic (1953) who showed that which would control many species of marine bacteria. Spencer (1952) had already shown that it was relatively harmless to Isochrysis at this concentration.…”
Section: Resultsmentioning
confidence: 88%
“…Despite the fact that the combination tested on T1 had been previously used (Spencer 1952, Borojevic 1966, Harms 1986, Roberts et al 2007, Pringault et al 2009, Trotted et al 2011), the concentration used had never been tested on invertebrate cultures. Spencer (1952) …”
Section: Discussionmentioning
confidence: 99%
“…Combinations of antibiotics such as penicillin and streptomycin have been widely used in cultivation with positive survival and growth results in the species of interest (Spencer 1952), with some authors adding neomycin (Droop 1967(Droop , agostini 2014 and chloramphenicol (Droop 1967), thus increasing the efficiency in inhibiting bacterial growth. On the other hand, the individual application of oxytetracycline hydrochloride has shown significant results in the reduction of bacterial diseases in fish (Pereira Jr. et al 2006).…”
mentioning
confidence: 99%
“…The media used were: (i) peptone sea water, (ii) peptone sea-water agar, (ill) casein sea-water agar, as described by Spencer (1952).…”
Section: Sterility Testingmentioning
confidence: 99%